Tidal Dynamics Control on Cold-Water Coral Growth: A High-Resolution Multivariable Study on Eastern Atlantic Cold-Water Coral Sites - Juva, Katriina; Flögel, Sascha; Karstensen, Johannes; Linke, Peter; Dullo, Wolf-Christian (Frontiers in Marine Science, 2020)
Cold-water coral communities form complex benthic ecosystems in a distinct part of the water column. The exact processes supporting reef growth and changes with time are still partly unsolved. Recent studies have suggested a tidally driven hydraulic control of flow over topographic features as a driver for local downwelling at cold-water coral sites. This mechanism forms a link between surface and coral growth depths and is a driver of resuspension of the bottom material. Only few studies have concentrated on how these processes vary with the health status and structure of the cold-water coral occurrences. In this study, we explore the processes over tidal cycles by analysing in situ stratification, hydrography and velocity data which we then combine with local topography from seven Lophelia pertusa dominated eastern Atlantic cold-water coral sites. The “quality” of coral sites varies from thriving reefs to declining and dead coral sites. We show that living and healthy corals are concentrated at sites, where local hydrodynamics create overturning and mixing which support food supply for filter-feeding corals.